Oil prices effects on Colombia’s main macroeconomic indicators - Maldonado Umaña, Luis Fernando (2016)
This research main purpose is to determine the effects of oil prices in an oil exporting economy with focus on the Colombian case. First of all, it will be determined if Colombia is a net oil exporter; then, the relevance of oil exports in Colombia’s economy will be determined in order to define if this commodity is important for the Colombian economy. After proving the importance of oil in the country’s economy, an econometric model will be applied to demonstrate if the hypothesis that there is a direct relationship between oil prices and Colombia’s economic performance is true. The variables that are going to be tested in this paper are Consumer Price Index (CPI), Gross Domestic Product (GDP) and Balance of Payments (BOP) which captures the net effect between exports and imports plus net capital flows. If the hypothesis that oil prices directly affect Colombia’s economic performance is proved to be right, very close attention must be paid because oil is a non-renewable source of energy and unless new oil deposits are discovered, the commodity will begin to drain and an even higher negative effect can be observed in the future if the country’s economic focus doesn’t change before existing oil is all used up along with the county reserves. If the country doesn’t concentrate in diversifying its economy, Dutch disease can be very harmful because the economy will be in very bad shape when oil dries up or prices become very low that country revenues plummet and extracting this commodity is not profitable enough and production and further exploitation will simply be inexistent.